การกำหนดค่าเสียหายทางจิตใจในคดีละเมิดทางปกครอง - ณัฐวิภา บำรุงทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The thesis is aimed to study the problem in determining the mental damage in case of administrative violation. The outcome of study has revealed that Thailand has the problem relating to the issue of being injured person, the protection of the rights of injured person, lack of the mental damage - determining law including a mean and criteria in determining compensation for the appropriately - mental damage. At present, Even if The Administrative Court begin accepting that when the public officials, performing their duties might cause mental damage in consequence of bodily, sanitation, liberty, reputation damage, and rights of injured person and the Court shall decide the case, rendering the administrative authorities, on the other hand, public office to which the officials attaches to pay compensation for mental damage to person only who sustain the consequence of the violation directly and determining the compensation on merely some specific case, seeming to be contrary to the fact, equality and incompatible with the fairness, policy of law and criminal justice of the State. All these are not considered, rendering justice to the injured person perfectly because the civil law countries like Thailand, namely, France, and Germany that the Courts have decided the cases, ordering the State to pay compensation for mental damage to the plaintiff who sustains the damage from any other grounds for an amount more than that of Thailand including paying compensation for damage to intimate persons of injured person such as father, mother, husband, wife and child which is seem to be a progress in term of rendering the justice for the people.Consequently, the writer proposes the approach to solve the said problems on 2 ways, namely, firstly the Legislative and relevant authorities should amend the relevant laws, regulations and ways of practice in respect of determining compensation for mental damage in a case of administrative violation in concrete way and secondly, the Judge of The Administrative Court might lay down the general legal rule on the said issues by ways of making a court decision, containing relevant concepts, theories on the public law and the general principle on administrative tort pursuant to the provision of the Civil and Commercial Code to be applied on mutatis mutandis as well as not against the principle of public law.